CD4 count at presentation for HIV care in the United States and Canada: are those over 50 years more likely to have a delayed presentation? - Althoff, Keri N; Gebo, Kelly A; Gange, Stephen J; Klein, Marina B; Brooks, John T; Hogg, Robert S; Bosch, Ronald J; Horberg, Michael A; Saag, Michael S; Kitahata, Mari M; Eron, Joseph J; Napravnik, Sonia; et al. (AIDS research and therapy, 2010)
ABSTRACT: We assessed CD4 count at initial presentation for HIV care among ≥50-year-olds from 1997-2007 in 13 US and Canadian clinical cohorts and compared to <50-year-olds. 44,491 HIV-infected individuals in the North American AIDS Cohort Collaboration on Research and Design (NA-ACCORD) were included in our study. Trends in mean CD4 count (measured as cells/mm³) and 95% confidence intervals ([,]) were determined using linear regression stratified by age category and adjusted for gender, race/ethnicity, HIV transmission risk and cohort. From 1997-2007, the proportion of individuals presenting for HIV care who were ≥50-years-old increased from 17% to 27% (p-value < 0.01). The median CD4 count among ≥50 year-olds was consistently lower than younger adults. The interaction of age group and calendar year was significant (p-value <0.01) with both age groups experiencing modest annual improvements over time (< 50-year-olds: 5 [4 , 6] cells/mm3; ≥50-year-olds: 7 [5 , 9] cells/mm³), after adjusting for sex, race/ethnicity, HIV transmission risk group and cohort; however, increases in the two groups were similar after 2000. A greater proportion of older individuals had an AIDS-defining diagnosis at, or within three months prior to, first presentation for HIV care compared to younger individuals (13% vs. 10%, respectively). Due to the increasing proportion, consistently lower CD4 counts, and more advanced HIV disease in adults ≥50-year-old at first presentation for HIV care, renewed HIV testing efforts are needed.